Cu@Sn nanostructures based on light-weight current collectors for superior reversible lithium ion storage. Issue 24 (17th February 2016) - Lin, Ruoxu; Zhang, Shichao; Ren, Yanbiao; Wu, Xiaomeng; Fang, Hua; Wei, Xin
Abstract : The welding process makes good progress to reduce the sheet resistance, which ensures the effective diffusion of Li-ions and electrons. Abstract : A binder-free method is applied to avoid the huge irreversible capacity of Sn-based composite anodes in this paper. We report two types of copper-based current collector: (i) a light and flexible current collector, which is fabricated from copper nanowires (CuNWs), and (ii) Cu foam with copper nanowires grown on it. The charge capacity of the thin CuNW sheet based Sn–Cu composite anode remains above 760 mA h g −1 after 60 cycles with a relatively stable coulombic efficiency fluctuating around 97%. The Cu foam based composite anode also shows a good capacity retention of 79.8% after the same test, compared with the Cu foil based anode. According to the good rate performance and the light weight of the composite electrode, the CuNW sheet based current collector may be a promising material in energy fields in the future.